1993
DOI: 10.1161/01.atv.13.1.70
|View full text |Cite
|
Sign up to set email alerts
|

Arterial intimal hyperplasia after occlusion of the adventitial vasa vasorum in the pig.

Abstract: Oxygenation of the arterial wall is provided by diffusion of oxygen outward from the main vessel lumen and inward from the adventitial vasa vasorum. In a group of four Yucatan miniature pigs the oxygenation profiles across the superficial femoral arteries were recorded by polarographic oxygen microelectrodes. The profiles obtained suggested a relatively poorly oxygenated media (a trough value of approximately 25% that of the intimal oxygenation) with a progressive rise in oxygenation toward the intimal and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
108
1
5

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(118 citation statements)
references
References 32 publications
(20 reference statements)
4
108
1
5
Order By: Relevance
“…Later in the disease process, increased diffusion distances, attributable to intimal thickening as well as a high consumption of oxygen 8 and glucose 9,10 by foam cells, could additionally aggravate energy metabolic predicaments and contribute to the development of a necrotic core. Supportive of this hypothesis, hypoxic zones have been demonstrated in situ in the normal pig arterial wall 11 as well as in vitro [12][13][14] and in vivo 15 in rabbit atherosclerotic plaques. However, ATP production may be maintained under hypoxic conditions via anaerobic breakdown of glucose and glycogen, but this could lead to a potentially harmful accumulation of lactate.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Later in the disease process, increased diffusion distances, attributable to intimal thickening as well as a high consumption of oxygen 8 and glucose 9,10 by foam cells, could additionally aggravate energy metabolic predicaments and contribute to the development of a necrotic core. Supportive of this hypothesis, hypoxic zones have been demonstrated in situ in the normal pig arterial wall 11 as well as in vitro [12][13][14] and in vivo 15 in rabbit atherosclerotic plaques. However, ATP production may be maintained under hypoxic conditions via anaerobic breakdown of glucose and glycogen, but this could lead to a potentially harmful accumulation of lactate.…”
mentioning
confidence: 75%
“…Consequently, glycogen concentrations were high in the layers where in vivo oxygen concentrations would be expected to be low. 11 It has recently been shown that culture of rat tail arteries under hypoxic conditions leads to a very pronounced upregulation of the glycogen stores. 29 A possible explanation of our finding could thus be that the hypoxic microenvironment in the mid media leads to a local upregulation of the glycogen stores in these layers.…”
Section: Glycogen As An Energy Substratementioning
confidence: 99%
“…In addition, while performing the anastomotic procedure, local hypoxia is induced when vascular clamps are in place and when the adventitial vasa vasorum are disrupted during transection of the aorta. [7][8][9] In the present study, we characterized the role of tension on the aortic end-to-end anastomosis and found that tension, created by resection of a ring of aorta, profoundly increased the severity of vascular remodeling. The vascular lesions were characterized by medial calcification with chondroid metaplasia and luminal stenosis was most severe at 2 months postsurgery.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to tension at the site of anastomosis. Moreover, rupture of the adventitial vasa vasorum by transection of the aorta causes prolonged local hypoxia at the anastomotic site 7,8 as hypoxia of the injured arterial wall has been demonstrated in an experimental model even at 2 weeks after an arterial end-to-end anastomosis. 9 The hypoxia-regulated glycoprotein vascular endothelial growth factor (VEGF) 10 is a potent angiogenic factor that acts through 2 receptors, Flt-1(VEGFR-1) and Flk-1(VEGFR-2).…”
mentioning
confidence: 99%
“…37,38 A number of different animal models of atherosclerosis rely on rendering the vessel wall hypoxic via the occlusion of the vasa vasorum, which results in the initiation of medial necrosis, intimal proliferation and the formation of hyperplastic lesions. 38,39 Contraction of vasa vasorum by locally formed angiotensin II in the adventitia may initiate pathological changes in the vessel wall. In diseased coronary arteries, exhibiting early and intermediate atherosclerotic lesions, ACE was detected largely in regions of fat laden macrophages and in association with T-lymphocytes.…”
Section: Chymase Activity and Localisation In Human Blood Vesselsmentioning
confidence: 99%